FINANCIAL AWARENESS OF STUDENTS ENTERING HIGHER EDUCATION BASED ON THE RESULTS OF A QUESTIONNAIRE RESEARCH - Habil, Agnes Csiszárik; Varga, János (PEOPLE: International Journal of Social Sciences, 2019)
The definition and the importance of the financial literacy and the financial awareness arises increasingly in connection with the economic crisis. When we try to analyse the events of the crisis, the most frequently asked question is, that who and to what extent is responsible for the escalation. On the side of banks we should say, that the main responsible participants were the borrowers, who bought the banking products with their insufficient financial knowledge. Is this criticism true, or the banks’ greed is the main reason, as the borrowers think? The banking products are very diverse and multifaceted, so the choice between them is not easy. The crisis has highlighted the fact, that without a stable financial knowledge it is very difficult to navigate in a globalized financial markets. Stable financial knowledge is essential for financial products to avoid the next financial crisis similar to the one in 2008. The role of the education system is unquestionable in all levels to acquiring and consolidating this knowledge, but the banks and central banks have an important role in this work as well. Hungarian people are often criticized because of an insufficient financial knowledge, but this problem is not mainly Hungarian, it is a big question all over the world. The aim of this study is to present the results of a questionnaire survey carried out in the Hungarian higher education